A survey of challenges and career aspirations of clinical dental students in Nigerian universities - O. O. Orenuga; O. O. daCosta (Nigerian Dental Association, 2009)
Objective: The study assessed undergraduate challenges and career aspirations of clinical dental students in Nigerian Universities. Method: A cross-sectional study in which all clinical dental students were evaluated. Data collection was by self-administered questionnaires distributed to the study population, which required demographic information location of dental school, entry qualification, choice of dentistry as a career, assessment of the dental programme and improvements suggest to make a difference in the programme. Result: There were 197 respondents, 98 males (49.7%) and 99 females (50.3%). Male: female was 1:1.01, mean age was 24.9 (+2.8). The majority, 191(97.0 %) were admitted through the Joint Admission Matriculation Board Examinations (JAMB-E). Benin dental school had the highest number of students, 77 (39.1%). One hundred and ninety-four (98.47%) of these Nigerian students were from the southern geo-political zones of the country. Undefined curriculum (23.86%), lack of dental materials (20.3%) and faulty equipment (18.78%) were the commonest constraints reported by the students during the undergraduate training. The need for improved clinical teaching and supervision by consultants was recommended by 31.47% of the students. Significantly more females wanted to specialize in paedodontics (p=0.00) and more males in oral and maxillofacial surgery (p=0.00). Conclusion:  While provision of formal lectures was considered satisfactory in most of the dental schools, a definite need for improvement in the clinical aspect of training was reported by the students. This included chair side teaching and provision of materials for patient management. Lack of a well defined and specific curriculum was perceived as a major problem in some of the dental schools.